Graph analysis of diffusion tensor imaging-based connectome in young men with internet gaming disorder - Qin, Jiaolong; Wang, Shuai; Ni, Huangjing; Wu, Ye; Chen, Limin; Guo, Shuaiyi; Zhang, Fuquan; Zhou, Zhenhe; Tian, Lin (Frontiers in Neuroscience, 2023)
Although prior evidence has demonstrated that dysfunctional brain organization is related to internet gaming disorder (IGD), the neuroanatomical basis underlying IGD remains unclear. In this diffusion tensor imaging (DTI) study, we aimed to examine the alteration of white matter structural connectome and its association with Internet gaming characteristics in 47 male youths with IGD and 34 well-matched healthy controls. Two approaches (i.e., network-based statistic (NBS) and graph theoretical measures) were applied to assess differences in specific topological features of networks and identify potential changes in topologic properties, respectively. Furthermore, we explored the association between the alteration and internet addiction severity. The NBS analysis revealed widespread alterations of cortico-limbic-striatal structural connectivity networks in the youths with IGD: 1) an increased subnet1 comprising insula and the regions responsible for visual, auditory and sensorimotor functions, and 2) two decreased subnet2 and subnet3 comprising insula, striatum and limbic regions. Further correlation analysis showed a significant positive association between the mean fractional anisotropy-weighted connectivity strength of subnet1 and internet addiction test scores in IGD group. The present study extends our understanding of the underlying neuroanatomical correlates of IGD and highlights the role of cortico-limbic-striatal network in understanding the neurobiological mechanisms underlying this disorder.